THE INFLUENCE OF DEMOCRATIC PARENTING ON CHILDREN’S LINGUISTIC INTELLIGENCE: A CASE STUDY ON THE ABILITY TO USE CONJUNCTIONS AND INTERJENCTIONS IN AL AND RD: PENGARUH POLA ASUH DEMOKRATIK TERHADAP KECERDASAN LINGUISTIK ANAK: STUDI KASUS TERHADAP PENGGUNAAN KONJUNGSI DAN INTERJEKSI PADA AL DAN RD - Yuniarsih Yuniarsih; Eva Jeniar Noverisa; Diana Kartika (LLDIKTI Wilayah X, 2024)
Every child will experience a process of development and language acquisition from birth to adulthood. Language development is related to cognitive development which greatly influences the development of language skills (linguistic skills). Linguistic intelligence is also called language intelligence, namely the ability to use words effectively both orally and in writing. This intelligence includes sensitivity to the meaning of words, word order, sound, rhythm and intonation of spoken words, including the ability to understand the power of words in changing states of mind and conveying information (Gardner, 2011). The aims of this research is to describe linguistic intelligence in 8 year old children, as well as to determine their interpersonal abilities, level of critical thinking and parenting style factors that influence them. An overview of the communication development of children aged 7-8 years is expected to be provided by the research in order to inform parents about their children's developmental needs. The method used is a qualitative descriptive approach with data collection techniques through observation, recording stories and documentation. The unit of analysis in this research is two children with different linguistic abilities and parenting styles (AL and RD). The research results show the role of parenting styles in supporting children's linguistic skills by building a language environment that is appropriate to the development level of 8 years old children (early childhood stage). Democratic parenting style allows children to express their thoughts freely to their parents.